Notowania kontraktów terminowych na pszenicę konsumpcyjną na rynku FOREX jako przykład anomalii rynku kapitałowego - Balina, Rafał (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2011)
This article presents chosen examples of anomalies in the distribution of rates of return on the stock exchanges in the world, based on a review of literature. Moreover, author has shown that in the case of futures contracts on feed wheat listed on the FOREX market there are also anomalies in the distribution of rates of return. It was noted that the rate of return and the coefficient of variation for a given asset in the last four hours of trading are significantly higher than in the rest of the day